PENGGUNAAN MEDIA ANIMASI DALAM MATA PELAJARAN IPS KELAS VII SMP NEGERI 2 SUNGAI RAYA - Dian Pertiwi; Sulistyarini Sulistyarini; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe title of  this research was The use of animation media in Social science subject of 1st grade student in Junior High School 2 Sungai Raya. The problem in this research was how is the use of animation media in Social science subject of 1st grade student in Junior High School 2 Sungai Raya. The purpose of this research was to find out about the use of animation media in Social science subject of 1st grade student in Junior High School 2 Sungai Raya.The approach used in this research was qualitative research method with descriptive analysis. The techniques of data collecting were observation, interview and documentation study, while the tools of data collecting were observation guide, interview guide, documnetation, and camera. The results of this research showed that: (1) The planning for Social science learning using animation media went well, all stages implemented well; (2) Good respons from students in Social science learning using animation media proved by their interest and enthusiastic increased in following and participating in all learning activities; and (3) Positive effect from using animation media in Social science learning proved by animation media can attract students’ interest and motivate them, moreover students can have a better, faster, and easier understansing in learning material.Keywords: Animation Media, Social Science Subject, The Use of Learning Media